Congener- and isomer-specific Perfluorinated compounds in textile wastewater from Southeast China. (20th October 2021) - Gu, Chunjie; Xu, Chenye; Zhou, Quan; Shen, Chensi; Ma, Chunyan; Liu, Shuren; Yin, Shanshan; Li, Fang
Abstract: Perfluorinated compounds (PFCs) are largely used in textile auxiliaries for the water/oil repellent finishing and have been listed as substances of very high concerns globally. Quantifying the generations and emissions of PFCs from textile and dyeing enterprises is of great significance to realizing the cleaner production management. In this study, congener- and isomer-specific PFCs were measured in regulation tank influent and final effluent from 48 textile plants in the Yangtze River Delta, China. The median ∑17 PFC concentrations in influent and effluent were 428.5 and 268.0 ng/L, respectively. Short- and medium-chain homologues accounted for three-quarters of the total PFCAs in these wastewater samples. Isomeric fingerprints showed an overwhelming occurrence of linear isomers rather than branched ones for PFOA, PFOS and PFHxS. This implied that PFCs in textile wastewater might not be exclusively from a 3M electrochemical fluorination (ECF) source. Raw materials played an important role in PFCs distributions since significantly higher levels of PFHpA, PFHxA, PFNA, PFDA, PFUnDA and PFTrDA were found in wastewater from chemical fibre manufacturing than from manufacturing of other materials. There was no significant discrepancy in PFCs removal rates between different treatments techniques. Although ecological risk assessment revealed an absent health risks of PFCs from effluent in the short term, the implement of textile cleaner production warrants concern due to the high volumes of water per unit fabric for processing. The widespread PFCs occurrence in textile wastewater highlighted the urgency of PFCs removal and disposal. We also encouraged the replacement of synthetic substances with natural materials, adoptions of technical improvements, and innovations such as life cycle analysis or cluster process management in the development of the textile industry. Graphical abstract: Image 1 Highlights: Release behaviors of perfluorinated compounds from textile industry were studied. Congener and isomer diversity implied the shift production toward novel compounds. Current treatment systems cannot sufficiently remove these emerging chemicals. Perfluorinated compounds from textile effluent were at insignificant risks levels. Lifecycle cleaner production is needed to decline the textile emission burdens.